Plan de negocios para la creación de un restaurante temático en la fusión de la comida típica y gourmet en el cantón Latacunga, provincia de Cotopaxi, Ecuador. - Calvopiña Banda, Yadira Monserrat (2019)
The main objective of this research is to determine whether the application of the Canvas model to the achievement of the business plan focused on typical food merged with the gourmet one is the best model to launch the project; also it allows the researcher to determine the viability of this research since the Canvas model is a tool of vital importance to the structuring of how the business should be, how it will create value and therefore provide the researcher with an alternative for customers who are in Latacunga city, in others places in the country, also people who come from abroad to raise awareness of Ecuadorian culture, which range from 25 to 65 years old and who are considered the target segment and for being part of the population economically active. So, it is proposed to carry out the business plan focused on the Canvas Model, which allows the researcher to determine the viability of the creation of a new restaurant that offers different and exciting preparations concerning the service of typical merged food with the gourmet as well as the environment that will be created to publicize the diverse cultures that exist in Ecuador accompanied by a exquisite typical dish of our region with the proper studies of customer segment, value proposition, channel, relationship with customers, revenue stream, essential resources, key activities, alliances and costs, which are part of the Canvas Model. By reviewing the projected financial statements, it can be confirmed that it is a viable business since the IRR (Internal Rate of Return) gives a positive value of 19%, the NPV (Present Net Value) is $56,712.25, and the TMAR is less than the IRR which confirms that the project is ready to be carried out.